Nighttime and daytime blurred: hyperreality and kitsch in Las Vegas. II Parte. - Irazábal, Clara (Portafolio, 1970)
This study investigates the production of hyperreality and kitsch in the last generation of tourist/gambling developments in Las Vegas. In these environments, the distinctions between nighttime and daytime are purposely blurred or made insignificant trought theur manipulation for the creation of spectacle and the production of a sense of alienation from time and reality. This suspension of real time and space, is aimed at both facilitating the deceiving perception of false, constructed `naturesÂ´; and producing ideal sites for pleasure and consumption. I engage this exploration throug two main analytical concepts: hyperreality and kitsch. Building upon this theoretical framework, I propose the therm hyperkitsch2 to denote the phenomenon in Las Vegas, and I claim that peopleÂ´s fascination with hyperkitsch iconography that relates to the urban world results from their alienation from their real cities. Thus, in Las Vegas Strip, there are simulated urban landscapes upon where visitors enact fantasy lives and ease the emptiness and estrangement derived from conflicted urban identities and poor citizanship. The study is a contribution for understanding the current social crisis of urban identity formation-for both the human subject and the public sphere-amid the acceleration metamorphos of our contemporary culture of spectacle, hedonism and consumerism.